Determinants of Green HRM: An Analysis of Green Training, Green Performance Appraisal, Green Compensation and Green Recruitment - Syahridhan, Sayed (International Journal of Advanced Multidisciplinary, 2024)
The purpose of this literature research is to help future authors in determining human resource management research. The research article Determining Green Human Resource Management: Green Training Analysis, Green Performance Appraisal, Green Compensation, and Green Recruitment is a scientific literature article within the scope of human resource management. The approach used in this literature review research is descriptive qualitative. The data collection technique is to use literature studies or review relevant previous articles. The data used in this descriptive qualitative approach comes from previous research that is relevant to this research and comes from academic online media such as Thomson Reuters Journals, Springer, Taylor & Francis, Scopus Emerald, Elsevier, Sage, Web of Science, Sinta Journals, DOAJ, EBSCO, Google Scholar and digital reference books. In previous studies, 1 relevant previous article was used to review each independent variable. The results of this literature review article are: 1) Green Training affects Green HRM; 2) Green Performance Appraisal affects Green HRM; 3) Green Compensation affects Green HRM; and 4) Green Recruitment affects Green HRM.